Eksistensi Horja Mandailing di Era Globalisasi - Batubara, Muhammad Zusanri; Atem, Atem; Anam, M. Syaeful (Universitas Cenderawasih, 2023)
The vulnerability of local culture to global culture is increasingly dangerous due to the massive development of technology. The influence of globalization can change every element of human life. Horja as a Mandailing cultural heritage can be eroded by the influence of globalization. The sacredness of horja can always change towards profane due to the demands and needs in the era of globalization. This research aims to find out how horja in the life of Mandailing people and horja in the era of globalization. The type of research used is qualitative research with descriptive methods. Data collection techniques through observation, interviews, and literature studies. The data analysis technique used is descriptive analysis. The results concluded that horja is divided into three types, namely horja siriaon, horja siluluton or horja mambulungi, and horja siulaon. Dalihan na tolu is the most important part of horja implementation which consists of kahanggi, mora, and anak boru. The existence of horja in the globalization era takes place according to Mandailing customs and traditions. There are shifts and changes in the implementation of horja but not too significant. Shifts and changes that occur follow technological developments according to the demands of the times in the era of globalization.